Embodying a self-avatar with a larger leg: its impacts on motor control and dynamic stability - Vallageas, Valentin; Aissaoui, Rachid; Willaert, Iris; Labbe, David R. (IEEE transactions on visualization and computer graphics, 2024)
Several studies have shown that users of immersive virtual reality can feel high levels of embodiment in self-avatars that have different morphological proportions than those of their actual bodies. Deformed and unrealistic morphological modifications are accepted by embodied users, underlying the adaptability of one's mental map of their body (body schema) in response to incoming sensory feedback. Before initiating a motor action, the brain uses the body schema to plan and sequence the necessary movements. Therefore, embodiment in a self-avatar with a different morphology, such as one with deformed proportions, could lead to changes in motor planning and execution. In this study, we aimed to measure the effects on movement planning and execution of embodying a self-avatar with an enlarged lower leg on one side. Thirty participants embodied an avatar without any deformations, and with an enlarged dominant or non-dominant leg, in randomized order. Two different levels of embodiment were induced, using synchronous or asynchronous visuotactile stimuli. In each condition, participants performed a gait initiation task. Their center of mass and center of pressure were measured, and the margin of stability (MoS) was computed from these values. Their perceived level of embodiment was also measured, using a validated questionnaire. Results show no significant changes on the biomechenical variables related to dynamic stability. Embodiment scores decreased with asynchronous stimuli, without impacting the measures related to stability. The body schema may not have been impacted by the larger virtual leg. However, deforming the self-avatar's morphology could have important implications when addressing individuals with impaired physical mobility by subtly influencing action execution during a rehabilitation protocol.